Los valores éticos y morales y su incidencia en la disciplina de los estudiantes de octavo año de educación básica del centro educativo “Narciso Cerda Maldonado” cantón La Maná, periodo lectivo 2011-2012 - Morán Mora, Ruth Anabel (2014)
Ethical values and Morales are essential in the life of all human beings, are acquired from childhood, the family unit is the primary school to teach them, but unfortunately, with the advances of science and the need to provide a better quality of life, parents have neglected the upbringing of their children, leaving all the work to teachers today is very common that students do not have human values, which is alarming for the entire educational community because that they are a fundamental basis for the formation of the personality of children, born....